EVALUATION AND COMPARISON OF SCREENING TOOLS USED TO PREDICT THE ADVERSE OUTCOMES OF ELDERLY PATIENTS IN THE EMERGENCY DEPARTMENT - SANRI, ERKMAN (CARBONE EDITORE, 2021)
Introduction: The proportion of the geriatric population, who visited the emergency departments (EDs) more frequently and with more complicated problems, is increasing every passing day. The use of screening tools to identify high-risk patients among elderly patients gains importance as it facilitates the selection of appropriate treatment and follow-up. In this study, we evaluate and compare the predictive ability of the Identification of Seniors at Risk (ISAR) and the Silver Code (SC) screening tools in Turkey. Materials and methods: Patients aged 65-year and over who visited our ED over a ten-month period were enrolled. ISAR and SC tools were applied to participants following the initial medical assessment. Receiver operating characteristic (ROC) analysis was used to evaluate the predictive ability of the tools in short and long-term adverse outcomes such as ED re-visit, hospitalization, and mortality. These evaluations were performed following the initial ED visit, 1 and 6-month after the initial ED visit. Results: The median (IQR) age of 497 participants was 73.0 (68.5, 79.0), and %53.9 were women. ISAR was slightly better than SC in predicting all adverse outcomes, except hospitalization following the initial visit, with poor-fair results [area under the ROC curves (AUCs) between 0.62-0.78]. SC was excellent in predicting hospitalization following the initial visit (AUC: 0.90) and poor in all other outcomes (AUCs between 0.58-0.71). Conclusion: Although the results of our study underline that SC was excellent at predicting hospitalization following the initial ED visit, both tools were insufficient to make decisions for other adverse outcomes. Of course, this does not mean that the tools have no clinical value; but indicates that they are not suitable for clinical decision-making on their own and need improvements.
Keywords: Geriatric assessment; emergency department; screening; PROGNOSTIC STRATIFICATION; RISK; IDENTIFICATION; SENIORS